THE ROLE OF DIGITAL LITERACY IN LEARNING MEDIA ACCORDING TO ISLAM - Syukri, Muhammad; Putri, Yulita; Nurhuda , Abid (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2023)
Literacy aims to hone one's abilities and insights, besides that it is also a milestone in the rise of civilization in the western and Islamic world, especially in the current era known as modernity, and provides opportunities and challenges in everyday life as a form of technological development and digitalization. Therefore the purpose of this study is to describe the role of digital literacy in learning media according to Islam. The method used is a literature study with a descriptive approach, followed by collecting data, then analyzing the contents, then finally concluding. The results of the study show that the role of digital literacy in learning media according to Islam includes counteracting hoaxes circulating on social media, preventing bullying both verbally and non-verbally, counteracting online gambling that is rife around society, and minimizing internet addiction for everyone. people who cannot be separated from cyberspace and prevent pornography which can lead to sexual crimes commonly referred to as cybersex. The hope is that knowing the important role of digital literacy in the current era can increase the awareness of parents, educators, participants, and readers in general so that they can avoid the various evils above and can be wiser in using and utilizing technology that is growing rapidly at all times.